A SUGGESTED SUPPLEMENT TO AUDIT TEST PROGRAMS. - Carter, James G. (The Accounting Review, 1952)
For some years auditors in the United States have been expressing opinions based on test-checks of the accounting records. Various authorities have seriously questioned the results of auditing tests commonly employed and attempts have been made to develop statistically sound standards of auditing to guide the auditor in making his inferences. The author of this paper suggests that the methods proposed in this article be used as a supplement to present auditing procedures. In situations in which the risk of error is relatively high, the auditor might well consider for his own protection the use of methods presented here. The typical practitioner of today is unknowingly introducing his personal bias into his samples. True enough, the auditor is sampling, but his methods are those of purposive sampling. It is fairly typical for him to select for testing two months' transactions out of the year. The auditor examines the transactions for existence or absence of error. No attempt is made to classify the errors as bad, very bad, and terrible. The only classification is in terms of dollars and more precisely, in terms of whether the error is material or immaterial. The concept of materiality is a subjective determination by the auditor based upon the relevant factors.